The Evolution of Education in the Singularity Era: Facing the Opportunities and Challenges of Future Technologies - Wardani, Febri Pramudya; Sisca Widiyastuti; Hadassah Grace Ferisca; Tamariska Agape Scaferi; Lovely Olive Fesca (PT FORMOSA CENDEKIA GLOBAL, 2024)
The singularity technology revolution promises profound transformations in education. This article explores how singularity technologies, including artificial intelligence (AI), machine learning, augmented reality (AR), virtual reality (VR), and the Internet of Things (IoT), are impacting teaching and learning methods. Exploring aspects of personalized learning, greater accessibility, and enhanced collaboration, the article examines the impact of these technologies on students, teachers, and educational institutions. While offering great potential to improve the quality of education, the adoption of singularity technologies also presents challenges such as infrastructure readiness, data security, and implementation costs. Through case studies and in-depth analysis, the article provides a comprehensive insight into how education will evolve in the era of singularity technologies